Out From the Shadows – Resolution of the Taxonomy of the Family Cryomorphaceae - Bowman, John P. (Frontiers in Microbiology, 2020)
The family Cryomorphaceae for many years has been a poorly-defined taxonomic group within the order Flavobacteriales, phylum Bacteroidetes. Members of the Cryomorphaceae, apparently consisting of multiple-family level clades, have been mostly but not exclusively detected in saline ecosystems. The problems with the taxonomy of this group have stemmed from inadequate resolution of taxonomic groups using 16S rRNA gene sequences, sparse numbers of cultivated taxa, and limited phenotypic distinctiveness. The Genome Taxonomic Database (GTDB), which is based on normalized taxonomic ranks includes Cryomorphaceae as containing the genera Owenweeksia and Schleiferia. This is at odds with the official taxonomy that places these genera in the family Schleiferiaceae. The other Cryomorphaceae affiliated species have even more uncertain taxonomic positions including Cryomorpha ignava. To clarify the taxonomy of Cryomorphaceae genomes were generated for all type strains of the family Cryomorphaceae lacking such data. The GTDB-toolkit (GTDB-tk) was used to place taxa in the GTDB, which revealed novelty at the family level for some of these type strains. 16S rRNA gene sequences and concatenated protein sequences were used to further evaluate the taxonomy of the order Flavobacteriales. From the data the GTDB enabled successful clarification of the taxonomy of the family Cryomorphaceae. A number of placeholder families were given Latinized names. It is proposed that the family Cryomorphaceae is emended to include only the species Cryomorpha ignava. The family Schleiferiaceae is emended to account for the expansion of its membership. Luteibaculum oceani represents a new family designated Luteibaculaceae fam. nov. Vicingus serpentipes is the representative of Vicingaceae fam. nov. while Salibacter halophilus represents Salibacteraceae fam. nov.